Formation of a Tunnel under the Major Hepatic Vein Mouths during Removal of IVC Tumor Thrombus - Dmytro Shchukin (Case Reports in Urology)
This study describes a clinical observation of successful implementation of a new surgical maneuver: formation of a cross tunnel under the mouths of the major hepatic veins during removal of a tumor thrombus of the inferior vena cava. This surgical technique helps avoid the usage of   “piggyback” mobilization of the liver and the complications associated with it. However, for objective evaluation of this approach, a further clinical study is required.